Micro Risks and (Robust) Pareto-Improving Policies - Aguiar, Mark; Amador, Manuel; Arellano, Cristina (American Economic Review, 2024)
We provide conditions for the feasibility of robust Pareto-improving (RPI) policies when markets are incomplete and the interest rate is below the growth rate. We allow for arbitrary heterogeneity in preferences and income risk and a wedge between the return to capital and bonds. An RPI improves risk sharing and can induce a more efficient level of capital. Elasticities of aggregate savings to changes in interest rates are the crucial ingredients to the feasibility of RPIs. Government debt may complement rather than substitute for capital in an RPI. Our analysis emphasizes the welfare-improving qualities of government bonds versus explicit redistribution. (JEL D52, E43, E62, H20, H63)